Efektivitas Penggunaan Google Classroom Terhadap Hasil Belajar Siswa Mata Pelajaran Simulasi dan Komunikasi Digital (SIMDIG) Kelas X SMKN 1 Ampek Angkek - Putri, ‎Novri Yani; Zakir, Supratman; Melani, Melyann; Charles, Charles (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
The process of learning and teaching in general still use conventional methods. The results achieved are less than optimal and student activity is less visible. One of the efforts that can be made by the teacher so that students are able to participate in learning is by using Google Classroom, it can help students be more motivated and enthusiastic so that student learning outcomes increase. The formulation of the problem in this research is whether student learning outcomes in Simulation and Digital Communication (SIMDIG) subjects using Google Classroom are better than learning outcomes using conventional learning methods. This study aims to see the effect of using Google Classroom on student learning outcomes at SMK Negeri 1 Ampek Angkek. the one group pretest-posttest design. Sampling used a nonprobability sampling technique, namely purposive sampling using the F test where class X DKV was the experimental class and class X KKBT was the control class. From these results it is clear that the calculation obtained is that H0 is rejected because tcount = -4.122 is greater than ttable = 2.048 and the P-value = 0.000. From these results it can be concluded that,